A risk scoring system to predict coronary stent thrombosis. (4th May 2017) - Malik, Nikesh; Banning, Amerjeet S.; Belger, Mark; Fakhouri, Walid; Graham-Clarke, Peita L.; Banning, Adrian; Baumbach, Andreas; Blackman, Daniel J.; de Belder, Adam; Lefèvre, Thierry; Stables, Rod; Zaman, Azfar; et al.
Abstract: Objective: Stent thrombosis (ST) is a potentially life-threatening complication of percutaneous coronary intervention (PCI). We aimed to develop a scoring system to predict the risk of ST following PCI. Research design and methods: Odds ratios (ORs) for risk factors associated with ST were identified from a meta-analysis based on a systematic literature review, and through consensus expert opinion (Delphi–RAND method). The combined ORs were used to calculate risk scores for acute (within 24 hours), early (within 30 days) and late (31 days to 1 year) ST. Risk scores were validated against patient-level data from the TRITON-TIMI 38 study. Twenty risk factors were identified. Results: The most highly predictive factor for early and late ST was "incomplete duration of dual antiplatelet therapy". Derived total risk scores ranged from 0 to 22 for acute and early ST, and from 0 to 20 for late ST. Increasing scores were associated with an increasing risk of ST when applied to trial data. Model discrimination was 0.60 ( p = .0028), 0.67 ( p < .0001) and 0.66 ( p < .0001) for acute, early and late ST respectively, indicating good discriminatory power for predicting ST. Key limitations included a lack of published data on acute ST, resulting in a risk score for this time point being based predominantly on expert opinion, and that it was not possible to map all risk factors to variables collected in the TRITON-TIMI 38 study. Conclusion: Our weighted scoring system may help to stratify ST risk and individualize antiplatelet therapy in patients undergoing PCI.